2011
DOI: 10.1155/2011/748361
|View full text |Cite
|
Sign up to set email alerts
|

Retina and Omega-3

Abstract: Over the last decade, several epidemiological studies based on food frequency questionnaires suggest that omega-3 polyunsaturated fatty acids could have a protective role in reducing the onset and progression of retinal diseases. The retina has a high concentration of omega-3, particularly DHA, which optimizes fluidity of photoreceptor membranes, retinal integrity, and visual function. Furthermore, many studies demonstrated that DHA has a protective, for example antiapoptotic, role in the retina. From a nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 96 publications
(105 reference statements)
2
38
0
2
Order By: Relevance
“…DHA accounts for a significant fraction of omega-3 fats in the retina, and studies have found links between reduction in DHA with altered retinal function, including in RP [56,57]. This result is consistent with the numerous suggested protective roles of DHA in the retina, including anti-inflammatory, anti-angiogenesis, and anti-neurotoxic mechanisms [58].…”
Section: Metabolite/lipid Imaging Of Retinal Tissue Sections -To Invesupporting
confidence: 77%
“…DHA accounts for a significant fraction of omega-3 fats in the retina, and studies have found links between reduction in DHA with altered retinal function, including in RP [56,57]. This result is consistent with the numerous suggested protective roles of DHA in the retina, including anti-inflammatory, anti-angiogenesis, and anti-neurotoxic mechanisms [58].…”
Section: Metabolite/lipid Imaging Of Retinal Tissue Sections -To Invesupporting
confidence: 77%
“…It is of interest to note that dietary LPC-EPA markedly increased the omega 3 FAs not only in the brain but also in the retina, where Mfsd2a-mediated uptake is known to play a critical role (16). The protective role of EPA and DHA against retinopathies has been shown by several studies (41)(42)(43). The retina is unique in having very long-chain omega 3 FAs that give rise to pro-homeostatic molecules called elavonoids, which are essential for the integrity of the retinal pigmental epithelial cells (44).…”
mentioning
confidence: 99%
“…This is in line with the reports that DHA is the most abundant polyunsaturated fatty acid in the brain 30 and that upon crossing the blood-brain-barrier it is rapidly incorporated into phospholipids in particular into phosphatidylethanolamines 31 . Molecular images of DHA in whole-body sections confirm this and also highlight its localization within retina, where DHA is known to play structural and protective roles 32 . We also examined molecular images of lysophosphatidylcholine LysoPC (22:6) or LysoPC-DHA, another storage molecule of DHA (Figure 3b, also more images in METASPACE ).…”
Section: Exploring Spatial Metabolomes On the Levels Of Tissues And Omentioning
confidence: 61%